PENGAMPUNAN PAJAK (TAX AMNESTY) SEBAGAI UPAYA PENINGKATAN PENDAPATAN NASIONAL DARI SEKTOR FISKAL - Lukman Hakim Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Payment of taxes is the embodiment of a state obligation and role of the taxpayer to directly and jointly carry out tax obligations for financing the State and National development. In the last 11 year period, there were only two times the tax revenue target is reached. Moreover, the tax target is always misses. The peak occurred in 2015, when only 81.5 percent of tax revenue targets. All efforts deployed to achieve the target of taxation. One of the government's efforts to increase tax revenues that the government is launching a program of tax amnesty program (tax amnesty) in 2016.